1999
DOI: 10.1172/jci4824
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin fragments modulate monocyte VLA-5 expression and monocyte migration

Abstract: To identify the mechanisms that cause monocyte localization in infarcted myocardium, we studied the impact of ischemia-reperfusion injury on the surface expression and function of the monocyte fibronectin (FN) receptor VLA-5 (α 5 β 1 integrin, CD49e/CD29). Myocardial infarction was associated with the release of FN fragments into cardiac extracellular fluids. Incubating monocytes with postreperfusion cardiac lymph that contained these FN fragments selectively reduced expression of VLA-5, an effect suppressed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 52 publications
5
45
0
Order By: Relevance
“…After exposure to FNf, monocytes shed CD49e and are less able to migrate through collagenous matrices rich in native FN (23). FNf-induced loss of CD49e may also explain the failure of treated MNLs to penetrate deeply into FN-collagen matrices below the endothelial barrier in the present report.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…After exposure to FNf, monocytes shed CD49e and are less able to migrate through collagenous matrices rich in native FN (23). FNf-induced loss of CD49e may also explain the failure of treated MNLs to penetrate deeply into FN-collagen matrices below the endothelial barrier in the present report.…”
Section: Discussionsupporting
confidence: 46%
“…Recent studies have called attention to the possibility that proteolytic fragments or polymers of FN may be among the factors that influence leukocyte behavior in inflamed tissues (23)(24)(25). Certain FN fragments can stabilize and enhance the infectivity of cell-associated virus (24,25); other FN subunits can activate monocytes and cause them to release TNF-␣ through a protein kinase C-dependent signaling pathway (26 -30).…”
Section: Impact Of Fibronectin Fragments On the Transendothelial Migrmentioning
confidence: 99%
“…In experimental models, release of type I collagen fragments in the serum has been documented within 30 minutes after coronary occlusion (37). Fragmentation of components of the basement membrane, such as collagen IV, and of noncollagenous matrix constituents has also been demonstrated in the infarcted myocardium (38)(39)(40)(41). Low-molecular weight hyaluronan fragments exert potent proinflammatory actions in the infarcted region; impaired clearance of these fragments has been shown to prolong and accentuate proinflammatory signaling in leukocytes and vascular cells (42,43).…”
Section: Ecm During the Proliferative Phase Of Infarct Healingmentioning
confidence: 99%
“…have a promigratory effect on human neutrophils (22), and fragments of FN can modify the expression of VLA-5 and affect the migration of monocytes (26). We have shown that heparinase, a heparin sulfate-specific endoglycosidase, can degrade the ECM and release a specific disaccharide that inhibits delayed-type hypersensitivity in mice, and that this effect is accompanied by attenuation of the production of TNF-␣ by activated T cells (27).…”
Section: Discussionmentioning
confidence: 98%